The thermal neutron waves excitation in muldiplied media bounded by absorber - Vodyanitskii, A.A; Slyusarenko, Yu.V. (Вопросы атомной науки и техники, 2007)
An excitation of neutron waves by an external wave source in the active zone of the neutron field is investigated. It is found that the forced neutron waves are transformed into proper (eigen) neutron waves on the borders of the active area. The practical applications of results in noise diagnostics of active area of nuclear reactor are discussed. Зовнішнє хвильове джерело збуджує примусові нейтронні хвилі в активній зоні нейтронного поля. Ці хвилі перетворюються у власні нейтронні хвилі на межі активної зони. Результати мають практичні застосування в шумовій діагностиці активної зони реактора. Внешний волновой источник возбуждает вынужденные нейтронные волны в активной зоне нейтронного поля. Эти волны преобразовываются в собственные нейтронные волны на границе активной зоны. Результаты имеют практические приложения в шумовой диагностике активной зоны реактора.